fANOVA application for comparison of companies by the CEO turnover rates - Deinoravičiūtė, Urtė; Yasyreva, Anna (Lietuvos matematikos rinkinys, 2023)
The aim of this study was to analyze the data from the Nasdaq Baltic listed companies’ financial statements and to estimate if the CEO changes have a significant influence on the financial performance: profitability, indebtedness and stock price. Data was collected and financial ratios were computed for 34 companies during 2006 to 2021 (2008 to 2022 for stock prices). The companies were divided into 3 groups: ones that had no CEO changes over the period; those that had 1 or 2 and those with 3 or more. Point-wise ANOVA, fANOVA and fMANOVA were conducted. Both point-wise and functional ANOVA indicated that there is a significant difference of at least one group from the others in terms of ROA and EBITDA margin. After conducting two-sample tests, the group with 3 or more CEO changes was identified as having a significantly higher EBITDA margin than the others. Furthermore, a significant positive relationship between the stock price and the CEO turnover was uncovered in the function-on-scalar regression results.
Keywords: profitability; CEO turnover; functional data; fANOVA